Free‐radical Initialized Cyclization of 2‐(3‐Arylpropioloyl)benzaldehydes with Toluene Derivatives: Access to Benzylated 1, 4‐Naphthoquinones via Copper‐Catalyzed Cascade Reaction. Issue 2 (13th November 2020) - Zhu, Bingbin; Han, Hang; Su, Wei‐Ke; Yu, Chuanming; Jiang, Xinpeng
Abstract: A copper‐catalyzed cyclization reaction of 2‐(3‐arylpropioloyl)benzaldehydes was developed, leading to benzylated 1, 4‐naphthoquinones via radical‐triggered cascade cyclization. This example of an acylbenzylation involving internal alkynes could be carried out with a broad substrate scope and wide functional group tolerance. Abstract :